PENERAPAN TEKNIK SOSIODRAMA DALAM BIMBINGAN KLASIKAL UNTUK MENINGKATKAN HUBUNGAN SOSIAL TEMAN SEBAYA - Mutaqin, Miftahul Anwaril; Ningsih, Puji Rahayu; Winingsih, Evi; Sari, Unzhela Mustika Purwalis (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research explores the effect of applying sociodrama techniques in classical guidance on improving social relationships between peers in class X TBO students at SMK Negeri 3 Boyolangu, Tulungagung. By focusing on an important stage in adolescent development, where social interactions play a central role in their psychosocial well-being, this research applies the Guidance and Counseling Action Research Approach. Through two intervention cycles involving planning, implementation, observation, and reflection, we thoroughly explored the impact of sociodrama techniques. Data collected through questionnaires before and after the intervention, analyzed using the Wilcoxon test, revealed a significant increase in students' abilities in social interaction. These findings highlight the important role of innovative classical guidance in helping students face their social challenges and improving the quality of social interactions in the educational environment. This research not only makes an important contribution in deepening understanding of the role of guidance and counseling in supporting students' social-emotional development in adolescence, but also has relevant practical implications for the implementation of guidance services in schools. Thus, the results of this research not only add to academic knowledge, but also provide practical guidance for educational practitioners to design more effective strategies in helping students face the complexity of their social world.